Evaluating the Process and Outcomes of Disaster Preparedness Knowledge Acquisition Through Self - Instructional Modules Among Nursing Students in Tamil Nadu - Gadre, Pallavi; Parasuraman, Nithya (Journal of Educational Research and Policies, 2025)
The Study was conducted to evaluate the effectiveness of self-instructional module on knowledge regarding disaster preparedness among B. SC Nursing students. The sample consisted of 60 B.SC Nursing students. B. SC Nursing students were selected by purposive sampling technique. It was one group Pre-Test and Post-tests design. At the end of the study there was no significant association between the level of knowledge with selected demographic variables such as sex and seen any disaster affected place in which the calculated value is less than the table value and significant at the level of 0.05 and shown significant association between the level of knowledge with selected demographic variables such as age, religion, years of course, previous knowledge about disaster, you undergone any in-service training in disaster preparedness, have you got any individual experience in disaster management relative living in disaster zone and how will you prepare yourself during disaster in which calculated value is greater than the table value and significant at the level of 0.05. it found to be significant increase in the knowledge level among B. SC Nursing students and self-instructional module is found to be effective.